Cohort profile: the ADAPT study, a prospective study of pregnancy preferences, pregnancy, and health and well-being in the southwestern USA - Corinne H Rocca; Heather Gould; Elizabeth Gonzalez; Diana G Foster; Isabel Muñoz; Miriam Parra; Lauren J Ralph (BMJ Open, 2024)
Purpose Significant methodological shortcomings limit the validity of prior research on pregnancy decision-making and the effects of ‘unintended’ pregnancies on people’s health and well-being. The Attitudes and Decisions After Pregnancy Testing (ADAPT) study investigates the consequences for individuals unable to attain their pregnancy and childbearing preferences using an innovative nested prospective cohort design and novel conceptualisation and measurement of pregnancy preferences. Participants This paper describes the characteristics of the ADAPT Study Cohort, comprised of 2015 individuals aged 15–34 years, assigned female at birth, recruited between 2019 and 2022 from 23 health facilities in the southwestern USA. Findings to date The cohort was on average 25 years old. About 59% identified as Hispanic/Latine, 21% as white, and 8% as black, 13% multiracial or another race. Over half (56%) were nulliparous. About 32% lived in a household with income